Diagnostic and prognostic value of circulating biomarkers in heart failure - Kovenskiy, Artur; Mukhatayev, Zhussipbek; Sailybayeva, Aliya; Bekbossynova, Makhabbat; Kushugulova, Almagul (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure (HF) represents a global health burden with distinct phenotypes characterized by varying left ventricular ejection fraction (LVEF). Despite shared endothelial dysfunction, heart failure with reduced (HFrEF) and preserved ejection fraction (HFpEF) exhibit fundamentally different pathophysiological mechanisms, comorbidity profiles, and treatment responses.MethodsThis systematic review and meta-analysis examine inflammatory, cardiac remodelling and congestion, and myocardial injury biomarkers across HF phenotypes, integrating data from 78 studies encompassing 58,076 subjects.ResultsOur analysis reveals a significant elevation of IL-6, TNF-alpha, and hs-CRP in HF compared to controls, with distinct biomarker profiles emerging between phenotypes. While inflammatory markers universally increase with disease severity, their utility in phenotypic differentiation remains limited due to substantial overlap. Comorbidity burden significantly influences inflammatory profiles, creating diagnostic challenges that multi-biomarker approaches may address. NT-proBNP, sST2, GDF-15, and cardiac troponins demonstrate complementary value when combined with inflammatory markers, potentially enabling more precise phenotypic classification.ConclusionOur findings highlight the central role of inflammation in HF pathophysiology while identifying critical knowledge gaps, particularly regarding HFpEF-specific inflammatory signatures. This comprehensive analysis provides a foundation for developing targeted immunomodulatory therapies and personalized diagnostic approaches in heart failure management.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025639405, PROSPERO CRD42025639405.